Graphene oxide as a tool for antibiotic-resistant gene removal: a review - Bytesnikova, Zuzana; Richtera, Lukas; Smerkova, Kristyna; Adam, Vojtech (Environmental science and pollution research international, 2019)
Environmental pollutants, including antibiotics (ATBs), have become an increasingly common health hazard in the last several decades. Overdose and abuse of ATBs led to the emergence of antibiotic-resistant genes (ARGs), which represent a serious health threat. Moreover, water bodies and reservoirs are places where a wide range of bacterial species with ARGs originate, owing to the strong selective pressure from presence of ATB residues. In this regard, graphene oxide (GO) has been utilised in several fields including remediation of the environment. In this review, we present a brief overview of resistant genes of frequently used ATBs, their occurrence in the environment and their behaviour. Further, we discussed the factors influencing the binding of nucleic acids and the response of ARGs to GO, including the presence of salts in the water environment or water pH, because of intrinsic properties of GO of not only binding to nucleic acids but also catalysing their decomposition. This would be helpful in designing new types of water treatment facilities.
Keywords: grafit; Graphite; chemické látky znečišťující vodu; Wastewater; Drug Resistance, Bacterial; Genes; Graphene oxide; Genes, Bacterial; bakteriální geny; čištění vody; Water Purification; Anti-Bacterial Agents; Antibiotics; Environment; Waste Water; odpadní voda; bakteriální léková rezistence; Nanomaterials; Pollution; antibakteriální látky; Water Pollutants, Chemical